2006
DOI: 10.1111/j.1399-3046.2006.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical guidelines for the management of extra‐hepatic portal vein obstruction

Abstract: The recent introduction of the meso Rex bypass raises a possible paradigm shift in the therapeutic approach to extra-hepatic portal vein obstruction (EHPVO). Long-term follow-up of patients with EHPVO has revealed a variety of complications including variceal hemorrhage, hypersplenism, biliopathy, growth/development retardation and neuropsychiatric disease. The meso Rex bypass restores physiologic blood flow to the liver. Thus, when feasible, the meso Rex bypass should be considered in patients with clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(105 citation statements)
references
References 12 publications
1
96
0
8
Order By: Relevance
“…It may thus be a treatment option in certain patients. 167 In chronic PVT (portal cavernoma) TIPS placement has been successful in 35%-80%. [168][169][170][171] TIPS is unsuccessful if the lumen of thrombosed portal vein is not catheterizable and cavernomatous vein is not amenable to dilatation.…”
Section: Tipsmentioning
confidence: 99%
“…It may thus be a treatment option in certain patients. 167 In chronic PVT (portal cavernoma) TIPS placement has been successful in 35%-80%. [168][169][170][171] TIPS is unsuccessful if the lumen of thrombosed portal vein is not catheterizable and cavernomatous vein is not amenable to dilatation.…”
Section: Tipsmentioning
confidence: 99%
“…It is also important to note that previous work suggests that >90% patency can be achieved with meso-Rex shunt operations. 14 The patients from our institution did not fare this well, requiring numerous reoperations and long-term anti-coagulation for shunt thrombosis. These operations were not done at our institution, but were referred to a center that does a high volume of pediatric portal hypertension surgery.…”
Section: Conflicts Of Interestmentioning
confidence: 90%
“…With the development of novel surgical techniques, such as the meso-Rex bypass, some groups have suggested an aggressive surgical approach to patients with extrahepatic PVT. 11,14,17 Conversely, numerous series have suggested that the vast majority of these pediatric patients do well long-term without surgery, even when they develop complications including bleeding from both esophageal and gastric varices. [18][19][20] In all, our work supports the contention that a rather conservative approach to the management of noncirrhotic portal hypertension is warranted.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…82 Rex shunt (mesenterico-left portal vein bypass) in children who have EHPVO is considered to be the treatment of choice because they restore normal portal flow to the liver. 83 Symptomatic portal hypertensive biliopathy is a definite indication for intervention and depends upon its presentation. Definitive treatment may be in the form of In childhood and early adult life, variceal bleeding, growth retardation, and hypersplenism are the main presenting clinical problems.…”
Section: Managementmentioning
confidence: 99%